Analisis pengembangan tenaga pendidik melalui penerapan konsep dasar metodologi pendidikan islam di MA Al-Amin - Muhammad, Amin Rais; Setiawan, Didy (Academy of Education Journal, 2024)
The choice of approach and method must be correct and appropriate according to the character and nature of the material to be presented. Therefore, the approaches and methods used by educators can be said to be successful if these approaches and methods can achieve the expected educational goals. The aims of this research are: (1) to find out the application of the basic concepts of Islamic education methodology at MA Al-Amin, (2) to find out what approaches to Islamic education are often applied by teaching staff at MA Al-Amin, (3) to find out the role of educators in learning development at MA Al-Amin. This research uses a descriptive qualitative approach method with the aim of drawing in-depth conclusions in the field. Qualitative research is natural research, using certain methods to describe a phenomenon that occurs. These methods include interviews, observation, and documentation. The results of this research show that (1) MA Al-Amin has implemented the basic concepts of Islamic education methodology through teaching carried out by teachers with the methods used including the exemplary method, story method, dialogue method, reward and punishment method and providing advice -advice, (2) The most prominent application of the Islamic education approach at MA Al-Amin is the philosophical and emotional approach, (3) In implementing each learning method, Madrasah Aliyah Al-Amin facilitates every teacher, both in the form of moral support and facilities. learning supporter. Apart from that, Madrasah Aliyah Al-Amin often holds teacher development coaching workshops.